The Proteasome Inhibitor Bortezomib Maintains Osteocyte Viability in Multiple Myeloma Patients by Reducing Both Apoptosis and Autophagy: A New Function for Proteasome Inhibitors. (14th December 2015) - Toscani, Denise; Palumbo, Carla; Dalla Palma, Benedetta; Ferretti, Marzia; Bolzoni, Marina; Marchica, Valentina; Sena, Paola; Martella, Eugenia; Mancini, Cristina; Ferri, Valentina; Costa, Federica; Accardi, Fabrizio; et al.
ABSTRACT: Multiple myeloma (MM) is characterized by severely imbalanced bone remodeling. In this study, we investigated the potential effect of proteasome inhibitors (PIs), a class of drugs known to stimulate bone formation, on the mechanisms involved in osteocyte death induced by MM cells. First, we performed a histological analysis of osteocyte viability on bone biopsies on a cohort of 37 MM patients with symptomatic disease. A significantly higher number of viable osteocytes was detected in patients treated with a bortezomib (BOR)‐based regimen compared with those treated without BOR. Interestingly, both osteocyte autophagy and apoptosis were affected in vivo by BOR treatment. Thereafter, we checked the in vitro effect of BOR to understand the mechanisms whereby BOR maintains osteocyte viability in bone from MM patients. We found that osteocyte and preosteocyte autophagic death was triggered during coculturing with MM cells. Our evaluation was conducted by analyzing either autophagy markers microtubule‐associated protein light chain 3 beta (LC3B) and SQSTM1/sequestome 1 (p62) levels, or the cell ultrastructure by transmission electron microscopy. PIs were found to increase the basal levels of LC3 expression in the osteocytes while blunting the myeloma‐induced osteocyte death. PIs also reduced the autophagic death of osteocytes induced by high‐dose dexamethasone (DEX) and potentiated the anabolic effect of PTH(1‐34). Our data identify osteocyte autophagy as a new potential target in MM bone disease and support the use of PIs to maintain osteocyte viability and improve bone integrity in MM patients. © 2015 American Society for Bone and Mineral Research.